Pathology of the Policy-Making Process in Sport for All in Iran - Mohammad Javadipour; Somayeh Rahbari (The Society of Aging and Physical Activity (SAPA), 2018)
Background. "Sport for all" is associated with the heart of the community and aims to spread joy and happiness, boost morale, increase motivation, promote healthy individual and social life, reduce family and social abnormalities, strengthen physical power, and eliminate mental problems for all people, including men and women, and old and young people. Objectives. This study aims to evaluate the pathology of the policy-making process in sport for all in Iran. Methods. The methodology of this study utilized an applied mixed-method study. The population of the study consisted of executives and experts of sports for all in Iran. In the qualitative study, by using targeted and criterion sampling methods, 16 subjects were selected as a sample. Data was collected by conducting interviews. Then, the data from the interviews by Streubert and Carpenter's method (2011) were coded and analyzed. In the quantitative study, the samples were selected by using a simple random sampling method; the data was collected by using a questionnaire that was extracted from qualitative research. Data analysis in this section was performed by using the SPSS software and the Friedman test. Results. In the qualitative study, the findings showed that the organizational components, beliefs and cultures, economic conditions, scientific analysis and interpretation of studies, and research were factors that affected the policy-making process of sport for all in Iran. The existing weaknesses of the policy-making process in sport for all in Iran included weak control and monitoring, weak structure, weak planning and execution, weak performance of media, limited financial resources, weak performance of human resources, rules, and limited partnership of academic and research centers. Conclusion. In general, the findings showed that the policy-making process for sport for all in Iran was associated with certain weaknesses and challenges; they must be recognized and modified based on scientific methods. Strengthening the close communication between the individuals responsible, policy-making organizations, and universities in the field have been suggested.